Sepsis and Septic Shock: Outcomes in Elderly and Very Elderly Intensive Care Patients - Burcu Candemir; Kamil İnci; Gülbin Aygencel; Melda Türkoğlu (Galenos Yayinevi, 2022)
Objective:The relationship between age and the development and outcome of sepsis and septic shock is unclear, especially in adults. There are few studies about the incidence, prognosis and mortality rates of sepsis in elderly and very elderly patients. In this study, we aimed to determine the effect of age on the outcome of sepsis and septic shock in elderly and very elderly intensive care unit (ICU) patients.Materials and Methods:This study was a retrospective observational study conducted in our medical ICU. Two hundred elderly and very elderly patients with sepsis and septic shock were included in this study.Results:The mortality rate related to sepsis and septic shock was 61.5% (123 patients). The most common site of infection was lung (56.5%, 113 patients), followed by urinary tract (35%, 70 patients). There was no significant difference between the elderly (61.2%, 82 patients) and the very elderly (62.1%, 41 patients) patients in terms of ICU mortality related to sepsis and septic shock (p>0.05). Sequential Organ Failure Assessment score on ICU admission [1.195 odds ratio (OR) and 1.052-1.358 95% confidence interval (CI), p=0.006], requirement of invasive mechanical ventilation on ICU admission (4.330 OR and 1.529-12.258 95% CI, p=0.006), renal impairment at the end of the ICU follow-up (6.457 OR and 1.795-23.233 95% CI, p=0.004) and the disability to feed orally in ICU (0.064 OR and 0.018-0.226 95% CI, p=0.0001) were found as independent risk factors for ICU mortality.Conclusion:According to our study, there was no significant difference between the elderly and the very elderly ICU patients with sepsis and septic shock in terms of mortality rates. However, the presence of organ damage during ICU admission and the development of complications during ICU stay significantly affected mortality.